Integrate the hierarchical cluster elliptic curve key agreement with multiple secure data transfer modes into wireless sensor networks - Hua Yi Lin (Connection Science)
Since sensor nodes in wireless sensor networks or Internet of things have limited resources, achieving secure data transmissions among nodes is a challenge. Hence, efficient key management schemes with lightweight ciphers are essential. Many asymmetric keys or public key mechanisms have been developed. However, they are unsuitable for secure group communications in wireless sensor networks, because sensor nodes are usually devoid of sufficient memory, CPU and bandwidth to deal with complex operations. In addition, only a few group key agreements are integrated into secure data transmissions. Therefore, a key agreement using the hierarchy-based cluster elliptic curve key agreement named HCECKA is proposed in this study to deal with secure data transmissions in wireless sensor networks. The presented security mechanism relies on elliptic curves instead of logarithmic curves, and utilises a lesser key length to accomplish similar security classification than Diffie-Hellman and Rivest Shamir Adleman cryptosystems. Simultaneously, the proposed scheme provides a rapid, efficient and dynamic group key synchronisation technique in plenty of sensor nodes with no need for reorganising the whole system key if members join or leave wireless sensor networks.